Expression of the 1-Aminocyclopropane-1-Carboxylic Acid Deaminase Gene Requires Symbiotic Nitrogen-Fixing Regulator Gene nifA2 in Mesorhizobium loti MAFF303099 - Nukui, Noriyuki (American Society for Microbiology, 2006)
Many soil bacteria contain 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, which degrades ACC, a precursor of the phytohormone ethylene. In order to examine the regulation of the acdS gene encoding ACC deaminase in Mesorhizobium loti MAFF303099 during symbiosis with the host legume Lotus japonicus, we introduced the β-glucuronidase (GUS) gene into acdS so that GUS was expressed under control of the acdS promoter, and we also generated disruption mutants with mutations in a nitrogen fixation regulator gene, nifA. The histochemical GUS assay showed that there was exclusive expression of acdS in mature root nodules. Two homologous nifA genes, mll5857 and mll5837, were found in the symbiosis island of M. loti and were designated nifA1 and nifA2, respectively. Quantitative reverse transcription-PCR demonstrated that nifA2 disruption resulted in considerably diminished expression of acdS, nifH, and nifA1 in bacteroid cells. In contrast, nifA1 disruption slightly enhanced expression of the acdS transcripts and suppressed nifH to some extent. These results indicate that the acdS gene and other symbiotic genes are positively regulated by the NifA2 protein, but not by the NifA1 protein, in M. loti. The mode of gene expression suggests that M. loti acdS participates in the establishment and/or maintenance of mature nodules by interfering with the production of ethylene, which induces negative regulation of nodulation.